Glycyrrhiza Genus: enlightening phytochemical components for pharmacological and health-promoting abilities - Rad, Javad Sharifi; Quispe, Cristina; Herrera Bravo, Jesús; Belén, Lisandra Herrera; Kaur, Rajandeep; Kregiel, Dorota; Uprety, Yadav; Beyatli, Ahmet; Yeskaliyeva, Balakyz; Kırkın, Celale; Özçelik, Beraat; Sen, Surjit; et al. (Hindawi Publishing, 2021)
The Glycyrrhiza genus, generally well-known as licorice, is broadly used for food and medicinal purposes around the globe. The genus encompasses a rich pool of bioactive molecules including triterpene saponins (e.g., glycyrrhizin) and flavonoids (e.g., liquiritigenin, liquiritin). This genus is being increasingly exploited for its biological effects such as antioxidant, antibacterial, antifungal, anti-inflammatory, antiproliferative, and cytotoxic activities. The species Glycyrrhiza glabra L. and the compound glycyrrhizin (glycyrrhizic acid) have been studied immensely for their effect on humans. The efficacy of the compound has been reported to be significantly higher on viral hepatitis and immune deficiency syndrome. This review provides up-to-date data on the most widely investigated Glycyrrhiza species for food and medicinal purposes, with special emphasis on secondary metabolites’ composition and bioactive effects.